Climate-safe refrigerants - Zhang Zhaohui; Wang Ruonan (Asian Development Bank Institute (ADBI), 2023)
Refrigerant is the working medium of refrigeration and air-conditioning systems. Currently, synthetic refrigerants are the dominant refrigerants for cooling, but the emissions from synthetic refrigerants into the atmosphere will destroy the ozone layer. The global refrigeration and air-conditioning industry is working on a refrigerant substitution based on the provisions of the Montreal Protocol. In selecting new alternative refrigerants, a high level of efficiency, safety, economy, and good climate performance, among other things, will be fully considered. This paper examines cases of countries implementing policies promoting the recycling and reuse of refrigerants. The paper also provides policy recommendations aimed at reducing environmental pollution caused by refrigerant leakage and discharge, as well as a list of climate-safe refrigerants.
Keywords: O33; 330; refrigerant; refrigerant substitution; climate-safe